The Gender-Based Differences in Vulnerability to Ambient Air Pollution and Cerebrovascular Disease Mortality: Evidences Based on 26781 Deaths - Guangcong Liu; Baijun Sun; Lianzheng Yu; Jianping Chen; Bing Han; Yizhuo Li; Jie Chen (Ubiquity Press, 2020)
The gender-based differences in the vulnerability to ambient air pollution have not been widely explored. This study aimed to investigate vulnerability differences to the short-term effects of PM2.5, PM10 and O3 between cerebrovascular diseases (CEVD) deaths of men and women. The general additive models (GAMs) and distributed lag non-linear models (DLNMs) were adopted, and both single-pollutant and two-pollutant models were performed to analyze the associations between ambient air pollution and daily CEVD deaths. Both models indicated that O3 was the most suspicious pollutant that could induce excess CEVD deaths, and women tended to be more vulnerable to O3. These results were confirmed by seasonal analysis, in which we also found both genders were more vulnerable to O3 in winter. The exposure-response relationships revealed that women were usually more vulnerable to ambient air pollution than men, and the exposure-response curves differed significantly between genders. Our findings suggested that more attention should be paid on the adverse effects of ambient O3, and the protection of women CEVD population against air pollution should be emphasized.